Partisipasi Pimpinan Informal dalam Implementasi Program Pembangunan Kampung di Papua (Studi pada Partisipasi Pimpinan Informasi pada Distrik Waibu Kabupaten Jayapura) - Stevanus Thane; Djumilah Zain; Armanu Thoyib; Mintarti Rahayu (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
The objectives of this research are: (a) to understand the respective roles of formal and informal leaders (ondoporo/Ondoafi) in development planning activities in the of Kwadeware villages, District Waibu, Jayapura Regency, Papua Province; (b) to understanding the nature of each formal leader (headman) and informal leader (ondoporo / Ondoafi) towards the implementation of development programs in Kwadeware villages, District Waibu, Jayapura Regency, Papua Province; (c) to build a model or a synergistic form of leadership based on the pillars of brotherhood between both formal and informal leaders in the ward Kwadeware, District Waibu Jayapura Papua Province. The research method used in this study was a descriptive qualitative design. The research location was Kwadeware villages, Waibu District, Jayapura. The result of the study showed that a figure in indigenous Ondoapi Sentani is known as the central figure for the entire life of the people who live under his teritory. Conflicts of dualism leadership between formal and informal leaders, should become a major force in building a collaborative leadership in Kampung synergistially. In solving various problems concerning the rights of indigenous peoples in the village, governments should give a greater role to the institutions of indigenous peoples as a mediation between the government and traditional leaders in resolving the various problems that lead to the formation of a conflict of interest between adat leaders (ondoapi ) and the village chief.Keywords: informal leadership, implementation of development programs